Play-Based Learning: Benefits and Challenges of its Implementation - Haile, Tekli Simon; Ghirmai, Daniel Jambo (European Scientific Journal, ESJ, 2024)
This study explores how Eritrean pre-school educators viewed and conceptualized play-based learning (PBL), the benefits, and challenges of its implementation. A semi-structured interview was conducted with nine teachers, six principals, and two pre-primary education curriculum developers. Interviews were thematically analyzed. The study found discrepancies between participants’ views and their implementation. Our findings indicate that most of the participants viewed PBL as incorporating both free-play and guided play. However, the result of this study revealed that free play cannot effectively be used as an instrument to teach lessons that have specific academic objectives such as numeracy and literacy skills. Besides, the researchers sought to investigate the actual practices of PBL and the study found that majority of educators were placed at the Child Adult Involvement Continuum extremes, free-play, and direct instruction. Furthermore, the result revealed that various challenges were teachers face as they try to implement PBL, but the most common barrier discussed by interviewees was the lack of awareness of parents and principals towards PBL. Finally, the study concluded that the reason teachers lie at the two extremes of the Child Adults Involvement Continuum could be due to their views towards PBL, and its benefits and the challenges they face in implementing it.